Država, učitelj in delo z nadarjenimi učenci: med poslanstvom in odgovornostjo - Kukanja Gabrijelčič, Mojca (Revija za elementarno izobraževanje, 2017)
The State, Teacher and Work with Gifted Learnes – between Mission and Responsibility. This paper describes the role, mission, competences, social intelligence and responsibility of the gifted and talented teacher in terms of working and developing gifted students. Emphasize particularly gifted student teacher profile, whose specific needs and characteristics demands an independent, responsible and generaly competent specialist. However, the teacher is not presented in terms of pedagogical skills or professional competences that are necessary in teaching gifted students, but from another perspective, by the Slovenian area often overlooked, ie. from his personal and social characteristics that are much more valuable than his intellectual (Vialle 1998). As modern school reforms has brought changes in the role of the teacher, we need to provide them ongoing continuing education.We have analysed and evaluated the content programs of permanent professional in– service training for teachers in primary school from year 2010 on and found many deficiences about their systematic teaching training in area of gifted and talented education.